Solving maximum weighted matching with capacity > 1 in GLPK - glpk

When solving a regular maximum weighted matching problem in GLPK, one would provide a DIMACS file and call glp_asnprob_lp with GLP_ASN_MMP. However, this will set all the constrains to <= 1, for example
Subject To
r_1: + x(1,9) + x(1,10) + x(1,12) <= 1
r_2: + x(2,10) + x(2,12) + x(2,13) <= 1
r_3: + x(3,11) + x(3,13) <= 1
r_4: + x(4,9) + x(4,12) + x(4,14) <= 1
I want each node to have a higher capacity (say 10), hence the constrains would be:
Subject To
r_1: + x(1,9) + x(1,10) + x(1,12) <= 10
r_2: + x(2,10) + x(2,12) + x(2,13) <= 10
r_3: + x(3,11) + x(3,13) <= 10
r_4: + x(4,9) + x(4,12) + x(4,14) <= 10
How do I go about it? I really don't want to have to build my own matrix.

Related

Solving the recurrence relation T(n) = 2T(n/2)+1 with recursion

I'm trying to find the big O of T(n) = 2T(n/2) + 1. I figured out that it is O(n) with the Master Theorem but I'm trying to solve it with recursion and getting stuck.
My solving process is
T(n) = 2T(n/2) + 1 <= c * n
(we know that T(n/2) <= c * n/2)
2T(n/2) + 1 <= 2 * c * n/2 +1 <= c * n
Now I get that 1 <= 0.
I thought about saying that
T(n/2) <= c/2 * n/2
But is it right to do so? I don't know if I've seen it before so I'm pretty stuck.
I'm not sure what you mean by "solve it with recursion". What you can do is to unroll the equation.
So first you can think of n as a power of 2: n = 2^k.
Then you can rewrite your recurrence equation as T(2^k) = 2T(2^(k-1)) + 1.
Now it is easy to unroll this:
T(2^k) = 2 T(2^(k-1)) + 1
= 2 (T(2^(k-2) + 1) + 1
= 2 (2 (T(2^(k-3) + 1) + 1) + 1
= 2 (2 (2 (T(2^(k-4) + 1) + 1) + 1) + 1
= ...
This goes down to k = 0 and hits the base case T(1) = a. In most cases one uses a = 0 or a = 1 for exercises, but it could be anything.
If we now get rid of the parentheses the equation looks like this:
T(n) = 2^k * a + 2^k + 2^(k-1) + 2^(k-2) + ... + 2^1 + 2^0
From the beginning we know that 2^k = n and we know 2^k + ... + 2 + 1 = 2^(k+1) -1. See this as a binary number consisting of only 1s e.g. 111 = 1000 - 1.
So this simplifies to
T(n) = 2^k * a + 2^(k+1) - 1
= 2^k * a + 2 * 2^k - 1
= n * a + 2 * n - 1
= n * (2 + a) - 1
And now one can see that T(n) is in O(n) as long as a is a constant.

Substitution method for solving reccurences

I have recently had trouble with understanding the substitution method for solving reccurences. I watched few on-line lectures about the problem, but sadly it did not tell me much (in one of them I heard that it is based on guessing, which made me even more confused) and I am looking for some tips. My objective is to solve three different reccurence functions using substitution method, find their time complexity and their values for T(32).
Function 1 is defined as:
T(1) = 1
T(n) = T(n-1) + n for n > 1
I started off by listing first few executions:
T(2) = T(2-1)+2 = 1+2
T(3) = T(3-1)+3 = 1+2+3
T(4) = T(4-1)+4 = 1+2+3+4
T(5) = T(5-1)+5 = 1+2+3+4+5
...
T(n) = 1+2+...+(n-1)+n = n(n+1)/2
Then I proved by induction, that T(1) = 1 using the formula for sum of the first n natural numbers, and then that it is also true for n+1. It was pretty clear to me, but I am not sure whether this is substitution method. Also knowing the formula T(n) = n(n+1)/2 I easily calculated T(32) = 528 and counted the time complexity, which is O(n^2).
In examples (2) and (3) I only need solution for n=2^k when k is a natural number, but it would be nice if you recommended me any articles showing how to get these for all n as well (but I suppose it is way harder than that).
Function 2 is defined as:
T(1) = 0
T(n) = T(n/2) + 1 for even n > 1
T(n) = T((n+1)/2) + 1 for odd n > 1
As I was allowed to prove it only for n=2^k and based on my gained knowledge I tried to do it following way:
T(n) = T(n/2) + 1
= T(n/4) + 1 + 1 = T(n/4) + 2
= T(n/8) + 1 + 2 = T(n/8) + 3
= T(n/16) + 1 + 3 = T(n/16) + 4
= T(n/2^i) + i // where i <= k, according to tutorials
And this is the moment where I get stuck and I cannot proceed further. I suppose that my calculations are correct, but I am not sure how should I look for a formula, which would satisfy this function. After I get the right formula, calculating T(32) or time complexity will not be a problem.
Function 3 is defined as:
T(1) = 1
T(n) = 2T(n/2) + 1 for even n > 1
T(n) = T((n – 1)/2) + T((n+1)/2) + 1 for odd n > 1
My calculations:
T(n) = 2T(n/2) + 1
= 2(2T(n/4)+1) + 1 = 4T(n/4) + 3
= 4(2T(n/8)+1) + 3 = 8T(n/8) + 7
= iT(n/2^i) + 2^i - 1
And again it comes to the formula, which I am not sure how should be rewritten.
Basically, does substitution method for solving reccurences means finding and iterative formula?
After restudying the topic I found what I did wrong and not to leave my question unanswered, I will try to do it.
The first function is calculated well, induction proof is also correct - nothing to add here.
When it comes to the second function where I got stuck, I did not
pay attention that I was actually using a substitution n=2^k. This
is how it should look:
T(n) = T(n/2) + 1
= T(n/4) + 1 + 1 = T(n/4) + 2
= T(n/8) + 1 + 2 = T(n/8) + 3
= T(n/16) + 1 + 3 = T(n/16) + 4
= T(n/2^k) + k
= T(1) + k
= k
Induction proof that T(2^k) = k works:
Base case: k=1, then T(2^1) = T(2) = 1. (it cannot be k=0, as 2^0 is not bigger than 1)
Inductive step: assume T(2^k) = k, we want to show T(2^(k+1)) = k+1. As 2^k=n, then 2^(k+1) = 2*2^k = 2n.
T(2n) = T(n) + 1
= T(n/2) + 1 + 1
= T(n/4) + 2 + 1
= T(n/8) + 3 + 1
= T(1) + k + 1
= k + 1.
Time complexity: O(log n)
T(32) = T(2^5) = 5
In the third function I missed that every time the function called
itself, the value has doubled.
T(n) = 2T(n/2) + 1
= 2(2T(n/4)+1) + 1 = 4T(n/4) + 3
= 4(2T(n/8)+1) + 3 = 8T(n/8) + 7
= 8(2T(n/16)+1) + 7 = 16T(n/16) + 15
= 16(2T(n/32)+1) + 15 = 32T(n/32) + 31
= 2^k*T(n/2^i) + 2^k - 1
= 2^k*T(1) + 2^k - 1
= 2^k + 2^k - 1
= 2^(k+1) - 1
Induction proof that T(2^k) = 2^(k+1)-1 works:
Base case: k=1, then T(2^1) = T(2) = 3. Original function T(2) = 2T(1)+1 = 2+1 = 3, so base case is true.
Inductive step: assume T(2^k) = 2^(k+1)-1, we want to show T(2^(k+1)) = 2^(k+2)-1. Similarly, as in the second function, 2^k=n, so 2^(k+1) = 2*2^k = 2n.
T(2n) = 2T(n) + 1
= 2(2T(n/2)+1) + 1 = 4T(n/2) + 3
= 4(2T(n/4)+1) + 1 = 8T(n/4) + 7
= 8(2T(n/8)+1) + 1 = 16T(n/8) + 15
= 2^(k+1) + 2^(k+1) - 1
= 2*2^(k+1) - 1
= 2^(k+2) - 1.
We could also take a look at first few elements for T(n), which are 1, 3, 5, 7, 9, etc., so T(n) = 2n-1
Time complexity: O(n)
T(32) = T(2^5) = 2^(5+1) - 1 = 64 - 1 = 63

Defining a particular polynomial ring in some CAS (Computer Algebra System)

I'm interested in defining the following polynomial quotient ring in some CAS (Singular, GAP, Sage, etc.):
R = GF(256)[x] / (x^4 + 1)
Specifically, R is the set of all polynomials of degree at most 3, whose coefficients belong to GF(256). Two examples include:
p(x) = {03}x^3 + {01}x^2 + {01}x + {02}
q(x) = {0B}x^3 + {0D}x^2 + {09}x + {0E}
Addition and multiplication are defined as the per ring laws. Here, I mention them for emphasis:
Addition: The corresponding coefficients are XOR-ed (the addition law in GF(256)):
p(x) + q(x) = {08}x^3 + {0C}x^2 + {08}x + {0C}
Multiplication: The polynomials are multiplicated (coefficients are added and multiplicated in GF(256)). The result is computed modulo x^4 + 1:
p(x) * q(x) = ({03}*{0B}x^6 + ... + {02}*{0E}) mod (x^4 + 1)
= ({03}*{0B}x^6 + ... + {02}*{0E}) mod (x^4 + 1)
= ({1D}x^6 + {1C}x^5 + {1D}x^4 + {00}x^3 + {1D}x^2 + {1C}x + {1C}) mod (x^4 + 1)
= {01}
Please tell me how to define R = GF(256)[x] / (x^4 + 1) in a CAS of your choice, and show how to implement the above addition and multiplication between p(x) and q(x).

computational complexity of T(n)=T(n-1)+n

I have to calculate the computational complexity and computational complexity class of T(n) = T(n-1) + n.
My problem is that I don't know any method to do so and the only one I'm familiar with is universal recursion which doesn't apply to this task.
T(0) = a
T(n) = T(n-1) + n
n T(n)
---------
0 a
1 T(1-1) + n = a + 1
2 T(2-1) + n = a + 1 + 2
3 T(3-1) + n = a + 1 + 2 + 3
...
k T(k-1) + n = a + 1 + 2 + ... + k
= a + k(k+1)/2
Guess T(n) = O(n^2) based on the above. We can prove it by induction.
Base case: T(1) = T(0) + 1 = a + 1 <= c*1^2 provided that c >= a + 1.
Induction hypothesis: assume T(n) <= c*n^2 for all n up to and including k.
Induction step: show that T(k+1) <= c*(k+1)^2. We have
T(k+1) = T(k) + k + 1 <= c*k^2 + k + 1
<= c*k^2 + 2k + 1 // provided k >= 0
<= c*(k^2 + 2k + 1) // provided c >= 1
= c*(k+1)^2
We know k >= 0 and we can choose c to be the greater of a+1 and 1, which must reasonably be a+1 since T(0) is nonnegative.

How do you get N(N+1) from N+1 + N + 1 + ... + N + 1 + N + 1?

How does:
1 + 2 + ... + N-1 + N
+ N + N-1 + ... + 2 + 1
---------------------------
N+1 + N+1 + ... + N+1 + N+1
equal N(N + 1)? Shouldn't it be 4N + 4 or 4(N + 1)?
It is N(N + 1).
Because you have N number of (N+1) terms.
If N is 4, sure. Otherwise you need to fill in the rest of the elided values that the ellipses represent.
i assume your notation means row 1
+ row 2 = row 3?
in this case, look at the columns. Each column of the first 2 rows adds up to n+1. there are n columns. thus row 1 + row 2 = n*(n+1)
Read the part about the early years of Carl Friederich Gauss here. He solved almost the same problem when he was in primary school.

Resources